Warning! graphic content a study on the impact of infographics on attention, appeal, and recall and comprehension - Espeleta, Jul Yan Marie L. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The potential of the infographics have not been thoroughly investigated especially in the context of libraries and information dissemination. To determine the viability of inforgraphics as an information tool, the research endeavored to study the variables that affect the attention, appeal, and recall and comprehension of infographics using an online survey, a focus group discussion, and expert interviews. The findings established that dominant elements were the recipient of the grab and linger attention of participants. User context were also factors in what was paid attention to in an infographic as well as what was appealing. The research had also found out that appeal had an effect on recall and comprehension, and that participants remember details about the material for more than two weeks. The need to know and understand basic design principles were reinforced in the findings as well.